Impact of Stakeholder Engagement Strategies on Project Success in Cameroon - Haar, Khalica (International Journal of Project Management, 2024)
Purpose: The aim of the study was to assess the impact of stakeholder engagement strategies on project success in Cameroon. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A study conducted on the impact of stakeholder engagement strategies on project success in Cameroon reveals several significant findings. Firstly, it underscores the critical role of stakeholder engagement in enhancing project success by fostering collaboration, building trust, and ensuring alignment with stakeholders' interests and expectations. Effective communication emerges as a key component, facilitating the exchange of information, addressing concerns, and promoting transparency throughout the project lifecycle. Moreover, the research highlights the importance of tailoring engagement strategies to the cultural context of Cameroon, emphasizing the need for sensitivity to local customs, values, and power dynamics. Additionally, the study identifies challenges such as resource constraints, bureaucratic hurdles, and resistance to change, which can impede successful stakeholder engagement. To overcome these obstacles, the adoption of inclusive approaches, capacity-building initiatives, and the establishment of clear accountability mechanisms are recommended. Implications to Theory, Practice and Policy: Stakeholder theory, social exchange theory and resource dependency theory may be use to anchor future studies on assessing the impact of stakeholder engagement strategies on project success in Cameroon. Develop guidelines and best practices for implementing stakeholder engagement strategies tailored to specific industries and project contexts. Advocate for the development of regulatory frameworks that incentivize organizations to prioritize stakeholder engagement in project planning and execution.